Photoactivation of Anticancer Ru Complexes in Deep Tissue: How Deep Can We Go?. Issue 45 (19th July 2017) - Sun, Wen; Thiramanas, Raweewan; Slep, Leonardo D.; Zeng, Xiaolong; Mailänder, Volker; Wu, Si
Abstract: Activation of anticancer therapeutics such as ruthenium (Ru) complexes is currently a topic of intense investigation. The success of phototherapy relies on photoactivation of therapeutics after the light passes through skin and tissue. In this paper, the photoactivation of anticancer Ru complexes with 671‐nm red light through tissue of different thicknesses was studied. Four photoactivatable Ru complexes with different absorption wavelengths were synthesized. Two of them (Ru3 and Ru4) were responsive to wavelengths in the "therapeutic window" (650–900 nm) and could be activated using 671‐nm red light after passing through tissue up to 16‐mm‐thick. The other two (Ru1 and Ru2) could not be activated using red light. Additionally, activated Ru4 caused inhibition of cancer cells. These results suggest that photoactivatable Ru complexes are promising for applications in deep‐tissue phototherapy. Abstract : Anticancer ruthenium (Ru) complexes can be photoactivated by 671‐nm light after passing through a 16‐mm‐thick tissue. The photoactivated Ru complexes can inhibit the growth of cancer cells. These results suggest that Ru complexes are promising anticancer agents for deep‐tissue phototherapy.